Establishment Methods and Application Evaluation of Animal Models in Reproductive Toxicology Research - HUANG Dongyan; WU Jianhui (Shiyan dongwu yu bijiao yixue)
Reproductive toxicology is a discipline that uses toxicological methods to study the mechanisms by which foreign substances interfere with the generation of eggs or sperm and their detrimental effects on offspring. Research includes evaluating the damaging effects of test substances on reproductive function of parents and the toxicity evaluation of offspring embryos. People are exposed to a wide range of drugs, chemicals and environmental pollutants on a daily basis, and determining whether these substances have reproductive toxicity is crucial for the health of future generations. Reproductive toxicology research is therefore critical. Given the specificity and importance of reproductive toxicity evaluation, corresponding institutions both domestically and internationally have issued guidelines, national standards, or industry standards, all of which involve animal experiments. In the study of reproductive system diseases, numerous animal models have been developed to investigate key reproductive organs, such as testicles and ovaries. Each model involves the selection of animals, the establishment of methods, and the quantification of evaluation indicators, and all have advantages and limitations. The choice of model should be based on experimental needs and the characteristics of the model. This paper summarizes commonly used animal models for reproductive and development toxicity evaluation in reproductive toxicology research, including rat models for fertility and early embryonic development toxicity, rat models for embryo-fetal development toxicity, rabbit models for embryo-fetal development toxicity evaluation, minipig models for embryo-fetal development toxicity, rat models for perinatal toxicity, zebrafish models for embryonic development toxicity, and models for evaluating ovarian toxicity induced by chemical drugs, radiotherapy, autoimmunity, and ovariectomy, as well as models for evaluating testicular toxicity caused by chemical drugs and environmental factors. The methods for establishing these models, their application scope, and characteristics are reviewed in order to provide references for relevant research applications.